Failure of probenecid to alter the pharmacokinetics of ceforanide. - Jovanovich, J F (1981)
This investigation evaluated the effect of probenecid on ceforanide concentrations in eight healthy volunteers. Each volunteer was given 1 or 2 g of ceforanide either alone or with 1 g of probenecid. Concentrations of ceforanide in plasma, urine, and saliva were then measured. Probenecid did not alter the plasma concentrations of ceforanide, nor did it affect the urinary excretion of this agent. Ceforanide was not secreted into saliva in any detectable amount either when administered alone or with probenecid. It is not clear why probenecid has a negligible effect on ceforanide concentrations in plasma. It may be that tubular secretion plays less of a role in the excretion of ceforanide than expected, or that the physical properties of ceforanide prevent probenecid from affecting its excretion.